1994
DOI: 10.3109/00498259409043256
|View full text |Cite
|
Sign up to set email alerts
|

Disposition in rat of a new fluorinated, biocompatible, non-ionic telomeric carrier

Abstract: 1. The disposition of the new fluorinated, biocompatible, non-ionic telomeric carrier trisacryl conjugate (F-TAC) labelled with 13C and 14C on the amide function has been studied in the rat after p.o. and i.v. administration. 2. After i.v. administration, excretion measurements have shown that radioactivity was eliminated mainly in the urine (69% within 24 h), and that faecal excretion was low (8% within 72 h). After p.o. administration, faecal elimination was significantly increased (30% within 72 h). No radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…This kind of molecule can lower the surface tension of water more than hydrocarbon-based analogues, but they do not exhibit any detergent power (Pucci et al, 1991). They have several advantages : because of their low MW (molecular weight), they should be able to cross biological membranes and no accumulation phenomenon in the organism should be noted (Maurizis et al, 1994;Chehade et al, 1996). It does not interact well with the alkyl chain of natural lipids (Barthélémy et al, 2002) but can handle integral membrane proteins in aqueous solution without any denaturation (Chabaud et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of molecule can lower the surface tension of water more than hydrocarbon-based analogues, but they do not exhibit any detergent power (Pucci et al, 1991). They have several advantages : because of their low MW (molecular weight), they should be able to cross biological membranes and no accumulation phenomenon in the organism should be noted (Maurizis et al, 1994;Chehade et al, 1996). It does not interact well with the alkyl chain of natural lipids (Barthélémy et al, 2002) but can handle integral membrane proteins in aqueous solution without any denaturation (Chabaud et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are obtained by free radical telomerization of an acryloyl monomer such as tris(hydroxymethyl)acrylamidomethane (THAM, 1), in the presence of an alkane/ fluoroalkanethiol as a transfer reagent. Previous biological studies have shown that multifunctional molecules obtained by this method exhibit physicochemical properties and biocompatibility, making them suitable for drug delivery systems [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…[31] A whole-body autoradiography performed on rat and mouse allowed us to confirm the ubiquitous biodistribution of THAM-derived telomers in all biological compartments except the brain. [32] Moreover, after intravenous (iv) or oral (po) administration to rat, these compounds were slowly released within 100 h, and no toxicity was observed. Finally, the anchorage of various antitumor agents, such as cytosine arabinoside (Ara-C) or 5-fluorouracil (5-Fu), to the polymeric backbone gave macromolecular prodrugs with improved bioavailability and a better therapeutic index than the parent drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, on the basis of the ability of telomers to reach the bloodstream after oral administration, [32] and considering that free thalidomide is more active when given orally, further investigation of N-(aminopropyl)amino-thalidomide telomers is necessary to specify both the best dose and mode of administration in the EAE mouse model of MS. Two factors could account for increased activity with compounds 18 and 19 after ip injection: enhanced general bioavailability due to structural modification of the parent thalidomide, and/or multiple appending of the active component on the same carrier. Considering the hydrophobic character of thalidomide, conjugation to a hydrophilic moiety might be expected to enhance activity.…”
Section: Multiple Sclerosis Animal Modelmentioning
confidence: 99%